Impact hammer applications in Istanbul metro tunnels - Tunçdemir, H. (Elsevier BV, 2008)
Abstract Hydraulic impact hammers have been used widely in Istanbul metro tunnels since 1992. This paper summarizes recent studies and explains the basic principles of the proper selection of hydraulic impact hammers. First data on 600 different hydraulic impact hammers available in the market are analyzed and the relationships between operational variables, such as hammer operating weight, impact energy, recommended excavation weight and size, are investigated in order to make some recommendations on how to calculate the efficiencies of impact hammers and to select proper hammer for a given job. A detailed study is also realized on Levent–Maslak tunnel drivages. Overall performance of tunnel drivages, the relation between Rock Mass Rating (RMR) and net breaking rate of hammers are also explained and compared with previous results obtained in other hydraulic hammer applications in Istanbul tunnel drivages. It is found that the net breaking rate of an impact hammer decreases linearly with RMR.